UPAYA MENINGKATKAN KEMAMPUAN HAFALAN PERKALIAN MELALUI PROGRAM BIMBINGAN BELAJAR PADA ANAK-ANAK DESA TANJUNG BENUANG - Sugeng Riyadi; Awatif; Hasmawati; Sukur; Sri Wahyuni (Hira Institute, 2025)
The ability to memorize multiplication tables is a fundamental aspect of learning mathematics, often posing a challenge for children in Tanjung Benuang Village. This study aims to enhance multiplication memorization skills through a structured and creative tutoring program. The program utilizes engaging learning methods, including multiplication songs, educational games, and flashcards. The research approach includes identifying needs, implementing the program, and evaluating outcomes. Results show a significant improvement in children's multiplication memorization skills, supported by weekly evaluations. Additionally, the program successfully increased confidence, independent learning abilities, and interest in mathematics. These findings suggest that tutoring programs can be an effective means of improving basic math skills in rural areas.